Email Duration, Batching and Self-interruption: Patterns of Email Use on Productivity and Stress - Mark, Gloria; Iqbal, Shamsi; Czerwinski, Mary; Johns, Paul; Sano, Akane (CHI '16 Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems, 2016)
While email provides numerous benefits in the workplace, it is unclear how patterns of email use might affect key workplace indicators of productivity and stress. We investigate how three email use patterns: duration, interruption habit, and batching, relate to perceived workplace productivity and stress. We tracked email usage with computer logging, biosensors and daily surveys for 40 information workers in their in situ workplace environments for 12 workdays. We found that the longer daily time spent on email, the lower was perceived productivity and the higher the measured stress. People who primarily check email through self-interruptions report higher productivity with longer email duration compared to those who rely on notifications. Batching email is associated with higher rated productivity with longer email duration, but despite widespread claims, we found no evidence that batching email leads to lower stress. We discuss the implications of our results for improving organizational email practices.